From the Magical Character of Speech to the Text of Writing: Mimetic Faculty and Profane Reading in Walter Benjamin - García Elizondo, Eduardo (2025)
The present paper proposes to analyze the intersection among speech (Sprache), writing and reading in Walter Benjamin’s rhetorical-theological and rhetorical-aesthetic writings. Based on this, through a path of expository interpretation, we will address how Walter Benjamin’s conception of the magical character of speech as such is elaborated in relation to the profane status of reading and the surrealist writing conceived through a rhetorical-materialist interpretation of the mimetic faculty. The exposition of these moments will be the starting point from which we will arrive at the following final considerations: that the surrealist writing is presented as a primordial aesthetic form to think about the critique of the analogical-proportional ideal of classicist tropology and the anthropological materialism of the discourse of Benjaminian criticism.